Investigation of the formation mechanisms of plasma electrolytic oxidation coatings on Mg alloy AM50 using particles. (1st April 2016) - Lu, Xiaopeng; Blawert, Carsten; Kainer, Karl Ulrich; Zheludkevich, Mikhail L.
Abstract: The growth of plasma electrolytic oxidation (PEO) coatings can be considered a complex process that includes discharge breakdown, sintering, and deposition process. In this work, inert SiO2 and La2 O3 particles were used as tracers to investigate the formation mechanisms of PEO coatings on Mg alloy AM50. The growth direction and kinetics of the coating formation are primarily controlled by the intensity and the number of discharges. High-intensity discharges enable the inward growth of the PEO coating rapidly. Low-intensity discharges allow the outward growth of the coating at a slow speed. At the initial stage of a treatment, conversion products form locally around the intermetallics and disseminate gradually. Discharges appear after reaching the breakdown potential, leading to rapid growth of the coating. The outward growth of the layer is non-uniform because the protruding conversion products are the last locations converted by the discharges. Inward growth of the layer occurs preferentially around intermetallic phases and the formation of the inner layer is related to the inward growth.